Characteristics of soil salinity and its impact on rice yield of coastal rice fields in West Aceh - Junita, Dewi; Kurniasih, Budiastuti; Putra, Eka Tarwaca Susila; Joko, Tri; Pazi, Ahmad Mustapha Mohamad (Journal of Degraded and Mining Lands Management, 2026)
Increasing soil salinity led to a decline in rice yield, particularly in the coastal areas of West Aceh affected by the 2004 tsunami. This study aimed to examine the characteristics of soil salinity in the coastal rice fields of West Aceh during the rainy and dry growing seasons, and to evaluate its impact on rice yield. Soil sampling was conducted using purposive sampling during two growing seasons: the dry growing season (April-September 2024) and the rainy growing season (October 2024-March 2025). Clustering analysis showed that three clusters (sodic and saline-sodic) formed during the dry season, while two clusters (sodic and non-saline non-sodic) formed during the rainy season. The Suak Pante Breuh site changed cluster membership, being sodic in the dry season and non-saline non-sodic in the rainy season. Among all soil chemical properties, soil electrical conductivity (EC) and sodium adsorption ratio (SAR) showed the strongest negative correlations with rice yield, particularly during the dry growing season (r = -0.55; r = -0.50). This study found that rice yield was more affected by salinity than by sodicity. This was illustrated in the Suak Timah 5 site, which was classified as sodic during the rainy season but showed similar rice yields to non-saline and non-sodic sites. In contrast, during the dry season, this site was classified as saline–sodic and recorded lower rice yields than other locations that were classified as sodic.